Expanding Models for Physics Teaching: A Framework for the Integration of Computational Modeling - Rebecca Elizabeth Vieyra; Colleen Megowan-Romanowicz; Kathi Fisler; Benjamin S. Lerner; Joe Gibbs Politz; Shriram Krishnamurthi (MDPI AG, 2024)
Teaching computation in science courses can enhance science education, but doing so requires that teachers expand the vision of their discipline beyond the traditional view of science presented in most curricula. This article describes a design-based research (DBR) program that included collaboration among high school teachers and professional development leaders in physics and computer science education. Through three years of professional development and teacher-led development, field testing, and refinement of integrated curricular resources, we have combined instructional modeling practices, physical lab materials, and computer programming activities. One of the outcomes is a co-created framework for the integration of computational modeling into physics that is sensitive to teachers' interests and expressed needs in addition to learning goals. This framework merges two evidence-based approaches to teaching: Bootstrap:Algebra, a web-based computing curriculum that emphasizes using multiple representations of functions and scaffolds that make the programming process explicit, and Modeling Instruction in physics, an approach that emphasizes the use of conceptual models, modeling practices and representational tools. In doing so, we uncover the need to balance teachers' visions for integration opportunities with practical instructional needs and emphasize that frameworks for integration need to reflect teachers' values and goals.